Tragic Seneca : an essay in the theatrical tradition - Boyle, A. J. (Anthony James) (Routledge, 1997)
Tragic Seneca undertakes a radical re-evaluation of Seneca's plays, their relationship to Roman imperial culture and their instrumental role in the evolution of the European theatrical tradition.